ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN RETRIBUSI PELAYANAN PASAR KELAS I DI KOTA MALANG (Studi Pada Pasar Besar, Pasar Madyopuro, Pasar Blimbing, Pasar Induk Gadang dan Pasar Dinoyo) - Sari, Fitria Nanda (Jurnal Ilmiah Mahasiswa FEB, 2018)
The purpose of this study was to determine the factors that have impact to the service marketretribution income from class I market in the city of Malang. This research is a field research orsurvey with quantitative approach, so that the data used is the primary data from thequestionnaires. The population in this research is market traders class I in the city of Malangclass I market traders in the city of Malang, with total sample as many as 100 traders in theCentral Market of Malang, Madyopuro Market, Blimbing Market and Primary Market of Gadang.The analysis technique used is path analysis and descriptive analysis. Variable used is theretribution rate for the service of the market, the quality level of service, knowledge andunderstanding of the retribution, the willingness to pay a retribution, and retribution income ofservice market. The results of this study indicate that the retribution rates for the service of themarket and the quality of service levels a positive and significant effect against on willingness topay a retribution and influential positive significant to retribution income of service market. Whilethe knowledge and understanding of the retribution a positive and significant effect to willingnessto pay a retribution but not significant effect against the retribution income of service market. Theresults of intervening testing shows that the willingness to pay a retribution can be provenintervening variable between the retribution rate for the service of the market, the quality level ofservice as well as knowledge and understanding of the retribution against the retribution incomeof service market.Keywords: retribution rate for the service of the market, quality level of service, knowledge andunderstanding of the retribution, willingness to pay a retribution, and retributionincome of service market